Interpersonal Trauma and Posttraumatic Stress Disorder among Black Women: Does Racial Discrimination Matter?. Issue 2 (15th March 2021) - Mekawi, Yara; Carter, Sierra; Brown, Brittney; Martinez de Andino, Ana; Fani, Negar; Michopoulos, Vasiliki; Powers, Abigail
ABSTRACT: There is evidence that the more frequent, severe, and chronic posttraumatic stress disorder (PTSD) symptomatology experienced by Black compared to White individuals cannot be explained by disparities in socioeconomic status or trauma exposure. One factor that may be important to consider is racial discrimination, which is associated with numerous negative mental health outcomes yet has not been studied in the context of interpersonal traumas for Black women. This study aims to fill this gap by examining the independent and interactive roles of racial discrimination and interpersonal trauma in predicting PTSD symptoms in a community sample of trauma-exposed, Black women ( n = 292). Consistent with the previous literature, we found that more frequent experiences of racial discrimination were associated with more severe PTSD symptoms overall ( r = .34) and by symptom cluster. Furthermore, we found a significant interaction between experiences of racial discrimination and experiences of interpersonal trauma ( b = .46, 95%CI[.04, .88], SE  = .28; Δ R 2  = .01, p = .03) such that the association between PTSD symptoms and interpersonal trauma was stronger at higher (+1 SD above the mean) levels of racial discrimination. This pattern was replicated for most PTSD symptom clusters. These results suggest that racial discrimination experiences exacerbate the association between interpersonal traumatic experiences and PTSD symptoms among Black women.